OCR product design for GCSE - Hancock, Geoff; Strickland, Austin; White, Bob (Abington Bookpoint, Ltd., 2009)
Foster understanding and problem-solving with this text which encourages the innovation and creativity at the heart of the OCR specifications.
Keywords: Design, Industrial -- Problems, exercises, etc; Industrial design -- Study and teaching; Industrial design